TINJAUAN YURIDIS TERHADAP PERJANJIAN ANJAK PIUTANG YANG TIDAK MEMENUHI KETENTUAN PASAL 613 KUH PERDATA - Syahrani Syahrani (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract           In the business world or in running an enterprise that money is one of the main factors in developing or maintaining its existence. However, sometimes suatuperusahaan not have sufficient funds or cash flow was not smooth, because the bills delayed up to several months.              Transfer of receivables on behalf of both the rise of credit transactions as well as the issue of trade transactions conducted with cessie and notification of the debtor. This notification is intended that the debtor is bound to the agreement made by the factor and the client.In the implementation of the factoring agreement without notification / Notifications, the client should perform his duty well, because otherwise these factors will greatly harmed. Though factors have been taking a very high risk by accepting the transfer of its receivables though without notification of the debtor. This is done by keeping in mind that the factors factor is cooperation partner companies that need funds immediately.